Memperkuat Nasionalisme Kebangsaan Perspektif Syekh Nawawi Al-Bantani dan M. Quraish Sihab - Muqit, Abdul (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2022)
This article discusses strengthening the nationalism of the perspectives of Sheikh Nawawi al-Bantani and M. Quraish Sihab using qualitative research methods with the type of whiteness research. The results of the study concluded that First, nationalism still has problems in terms of views among certain Islamic groups. This can be proven by the existence of radical movements and terrorism in Indonesia which still do not accept the concept of an Indonesian state order with pancasila ideology.Secondly, According to Quraish Sihab nationalism must be built with (1) the unity and unity of a nation. (2) a nation must have a hereditary origin. (3) have a language. In the Quran, it is explained that among the signs of the greatness of Allah Swt. are the variety of languages used by humans according to their respective tribes. (4) good customs must be traditionalized and discard bad customs. (5) loving a person is a sign of a person having perfect faith. Third, Sheikh Nawawi in his book was angry to explain that to strengthen and build nationalism, a peaceful state must be created. This is based on the postulate of the Quran surah Al-Baqarah verse 126.